2017
DOI: 10.1002/bdr2.1140
|View full text |Cite
|
Sign up to set email alerts
|

Regional differences in right versus left congenital heart disease diagnoses in neonates in the United States

Abstract: The prevalence of CHD diagnoses at birth in the US has increased, and regional differences in the prevalence of right defects appear to exist.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 38 publications
0
2
0
Order By: Relevance
“…On the other side, the South had the highest incidence of severe CHD in premature infants. The relative unavailability of antenatal screening for CHD and probably the lack of an opportunity to terminate pregnancy might have contributed to higher rates of CHD in preterm infants ( 16 ).…”
Section: Discussionmentioning
confidence: 99%
“…On the other side, the South had the highest incidence of severe CHD in premature infants. The relative unavailability of antenatal screening for CHD and probably the lack of an opportunity to terminate pregnancy might have contributed to higher rates of CHD in preterm infants ( 16 ).…”
Section: Discussionmentioning
confidence: 99%
“…Researches have shown that CHD is a major risk factor for infant mortality associated with BD and can lead to chronic disability, morbidity and increased medical costs 3 – 5 . It was previously reported that the prevalence of CHD was highest in Asia, second highest in Europe, and lowest in Africa, reflecting significant geographic differences 6 8 . Although environmental and behavioral components play a crucial role in the etiological progression of BD, additional research is still required 9 – 11 .…”
Section: Introductionmentioning
confidence: 92%